Мультимедійне мистецтво як засіб вираження архітектурно-сценографічних ідей Євгена Лисика - Воронкова, Іванна; Voronkova, Ivanna (Видавництво Львівської політехніки, 2021)
У статті висвітлено засоби мультимедійного мистецтва, які використовують при організації інтерактивного простору в будівлях громадського призначення. Розглянуто підходи формування інтерактивного предметно-просторового середовища із застосуванням мультимедійних об’єктів. Обґрунтовано можливість інтеграції сценографічних ідей Євгена Лисика з мультимедійними технічними засобами для створення інтерактивного динамічного дизайну як мистецького перформансу в інтер’єрі громадської будівлі.

The paper features the multimedia means employed to arrange an interactive space in public buildings. The advancement of computer technologies contributed to the development of the multimedia kind of art, with its versatility, multiplicity, and distinctness. Multimedia art can be integrated into the design of an objective-spatial environment in two ways: mechanical (implemented through the use of kinetic art objects, or kinetic deep spatia art) and multimedia (achieved through the use of sensory technologies and the creation of interactive projections onto surfaces). The author explored the approaches to the development of objective-spatial environment through multimedia objects: an imaginative approach based on the formation of the objective-spatial environment focusing on the generation of imagery and artistic expressiveness of the interior; functional utilitarian approach contributing to the arrangement of an objective-spatial environment dominated by the functionality of objects filling the interior. The paper reasons the possibility to integrate Yevhen Lysyk’s stage design ideas with the multimedia technical means to produce an interactive dynamic design as an artistic performance within the public building. It would contribute to the preservation of artworks by the brilliant scenographer still used in contemporary repertoire, and also add to the diversity of space, make bright imagery of the interior, and underlie its functionality. Moreover, with the help of modern digital technologies, we can increase the range of supporters of Yevhen Lysyk’s art to cultivate the feeling of the beautiful and the love for genuine art.
Multimedia art as a means of expression for architectural and stage design ideas by Yevhen Lysyk
Keywords: Євген Лисик; сценографія; архітектурно-сценографічні ідеї; мультимедійне мистецтво; інтерактивне предметно-просторове середовище; 3D-технології; Yevhen Lysyk; stage design; architectural stage design ideas; multimedia art; interactive objective-spatial environment; 3D technologies; 725; 747]; 75.054; 004.94-023.5